Estrategias neuropedagógicas para el aprendizaje lingüistico de los niños de 4 a 5 años de la Unidad Educativa Francisco Huerta Rendón cantón Babahoyo - Ponce Tapia, Vanessa Zeneida (2023)
During the child's development process, several difficulties appear, both external (environmental) and internal (biological), one of these problems is the development of language, therefore the present case study addresses the theme of "neuropedagogical strategies in the linguistic learning of children from 4 to 5 years of the Francisco Huerta Rendon Educational Unit", this topic becomes relevant because in Ecuador there is a high rate of alterations in linguistic development in early childhood, therefore, the implementation and development of of new neuropedagogical strategies in the institution, since it is observed that these problems are present in their school context, the present work aims to determine the impact of neuropedagogical strategies for language learning in children from 4 to 5 years of age of the educational unit Francisco Huerta Rendón, for this it was necessary to elaborate the theoretical framework from the var reliable neuropedagogical strategies and linguistic development, through the use of research methods which describes that the present work has a quantitative approach, in which descriptive and analytical research methods were used, in addition to the fact that the design is non-experimental, techniques were also used. data collection such as direct observation, survey, for this it was necessary to define the type of sample that was chosen, which was 35 parents to whom the survey was applied, which is reflected in the discussion of the results, in order to conclude that there is a need for the institution to implement neuropedagogical resources that facilitate linguistic development in the institution.